A study on the control path of financial research resource allocation based on Rahman model. Issue 4 (April 2023) - Zhang, Miting; Hou, Qiqi; Zhu, Tingting
Abstract: The participation of scientific research firms in transactions (research results) is a prerequisite for allocation of financial resources. Resources are allocated to projects with the greatest positive impact on social welfare. In this respect, the Rahman model is a useful method for allocating financial resources. It considers the dual productivity of a system and recommends allocating financial resources to the system with greatest absolute advantage. In this study, when the dual productivity of system 1 has an absolute advantage over that of system 2, the higher-level government will still allocate all financial resources to system 1, even if its total efficiency of research savings is lower than that of system 2. However, when the research conversion rate of system 1 is at a relative disadvantage but its total efficiency of research savings and dual productivity are both at a relative advantage, there may be a change in the government's allocation of financial resources. If the initial government decision time occurs before the jump point, system 1 will be allocated all resources until it reaches the jump point, but no resources once the jump point is crossed. Furthermore, the government will allocate all financial resources to system 1 if its dual productivity, total efficiency of research savings, and research conversion rate are at a relative advantage. Collectively, these results provide a theoretical basis and practical guidance for research specialization and resource allocation.